A Review of The Models of Land Development Process: The Structure Models - Ismail, Maziah (Fakulti Ukur dan Harta Tanah, 1996)
This is the final part of a three series paper reviewing the models Df land development process. One aspect which is lacking in all the three types of models discussed earlier is the focus on the way the production of the built environment is influenced by wider forces. It is suggested that the structure models seek to overcome this by focusing explaination of the development process within the perspective of the structural dynamics of the modes of production. However, they barely penetrate into the details of the events of the land development process and the network of the agency relationships. Therefore, it is concluded that the land development process is best explained within the critical framework of the institutional analysis as shaped by the structure and agency approach